Physics of atoms and molecles - Bransden, B. H.; Joachain, C. J. (New Delhi: Pearson, 2003)
The aim of this new edition is to provide a unified account of the subject within an undergraduate framework, taking the opportunity to make improvements based on the teaching experience of users of the first edition and cover important new developments in the subject.
References 1077-1082p.; Author index 1083-1092p.; Subject index 1093-1114
Keywords: Electron atoms; Molecuar structure; Quantum mechanics; General Science